Respuesta :
Answer:
y = 4 x + 13
Answer c is correct.
Step-by-step explanation:
We know that,
( -4 -3 ) ⇒ ( x₁ y₁)
(-3 1) ⇒ ( x₂ y₂)
You can use y = m x + c to find the equation.
Here,
m = slope
c = y- intercept
First, let's find the slope ( m ).
[tex]m =\frac{y_{1}-y_{2} }{x_{1}-x_{2} }[/tex]
[tex]m=\frac{-3-1}{-4-(-3)}[/tex]
[tex]m=\frac{-4}{-4+3}[/tex]
[tex]m=\frac{-4}{-1}[/tex]
[tex]m=4[/tex]
Now let us find the y intercept.
Let take ( -4, -3 ) coordinate for that.
y = m x + c
-3 = 4 × -4 + c
-3 = -16 + c
-3 + 16 = c
13 = c
And now let's create the equation.
y = m x + c
y = 4 x + 13
Hope this helps you.
Let me know if you have any other questions :-)
Answer:
y=4x+13
Step-by-step explanation:
m=(y2-y1)/(x2-x1)
m=(1-(-3))/(-3-(-4))
m=(1+3)/(-3+4)
m=4/1
m=4
y-y1=m(x-x1)
y-(-3)=4(x-(-4))
y+3=4(x+4)
y=4x+16-3
y=4x+13